A strategic approach for isolation and identification of plant growth promoting rhizobial strains from bhadrachalam forest area with respect to soybean (Glycine max) - SADAM DV SATYANARAYANA; KRISHNA MSR; PAVAN KUMAR PINDI (International Journal of Pharma and Bio Sciences, 2017)
Soil has been one of the major habitats for microbial communities in the ecosystem. It is a known fact that not more than one percentage of the microbial population has been explored. The quest of microbial exploration in the name of biodiversity is being carried, as a result of which more and more novel microbial communities are getting added to the literature. The aim of the study is to isolate and identify the crop specific Rhizobial strains for Glycine max from Bhadrachalam forest lands by an indigenous novel strategy to reduce the input cost in exploration of compatible strains for soybean avoiding serious constrain of biofertilizers i.e, shelf life. The results showed that the inoculated Rhizobia tremendously improved the plant growth when compared with control. Further phylogenetic analysis revealed that the contributing organisms are Bradyrhizobium japonicum, Bradyrhizobium elkanii, Sinorhizobium fredii, Bradyrhizobium yuanmingense, and Bradyrhizobium liaoningense sp. These Rhizobial species in the pure form exhibited high rate of plant growth at lab conditions followed by improved growth in low vegetative agriculture soils of the same geography. Therefore this method could be applied for the preliminary screening of compatible, species specific strains for any leguminous plants making the process easy and less expensive.